IN MEMORIAM - PROF. MOHAMMAD SHAFIQUE (1936 - 2022) - Idrees, Mohammad; Khattak, Shahid Masaud (Journal of Pakistan Psychiatric Society, 2022)
We share the news of Professor Mohammad Shafique’s passing with great sorrow. On the 2nd of August, 2022 at his home, our dear mentor and teacher passed away. Dr. Shafique was a pioneer for psychiatry in Pakistan, most notably his contributions were in the KPK province.He was the third Psychiatrist in Pakistan and first in KPK. He was a true Messiah to his patients and a role-model to his students. Like his name, he was the embodiment of kindness and compassion. He paved the way for future psychiatrists of the country by transforming psychiatric teaching and patient care as it was known. Many psychiatrists in Pakistan today have been mentored and taught by Dr. Shafique. He has been regarded as the father of psychiatry in Pakistan.In 1961, he went to England to pursue higher training in the field of Psychiatry, where he trained under Dr. John Hughes and Dr. Andy Wills at St. Cadoc’s Hospital in Cardiff, Wales. He received his Doctor of Psychological Medicine degree and returned to Pakistan in 1964 to accept the post of Medical Superintendent at Dhodial Mental Hospital. He developed it into a fully functional mental hospital and revolutionized psychiatric patient care across KPK by building new foundations for the system to stand on. Later on, he was made the Medical Superintendent of Peshawar Mental Hospital and he established the psychiatric OPD at Lady Reading Hospital. His efforts inside and outside the hospital changed the perspective on mental illness in KPK and across the country.